2019
DOI: 10.1038/s41598-019-53107-3
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting coupling within mycobacterial F-ATP synthases subunit ε causes dysregulated energy production and cell wall biosynthesis

Abstract: The dynamic interaction of the N- and C-terminal domains of mycobacterial F-ATP synthase subunit ε is proposed to contribute to efficient coupling of H+-translocation and ATP synthesis. Here, we investigate crosstalk between both subunit ε domains by introducing chromosomal atpC missense mutations in the C-terminal helix 2 of ε predicted to disrupt inter domain and subunit ε-α crosstalk and therefore coupling. The ε mutant εR105A,R111A,R113A,R115A (ε4A) showed decreased intracellular ATP, slower growth rates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…The growing interest in ATP synthase as a target and the emerging of BDQ resistance has resulted in a number of HTS and in silico screenings to identify additional options for ATP synthase inhibition and novel chemical entities for medicinal chemistry optimization, such as epigallocatechin [ 114 ], thiazolidones [ 115 ], and diaminoquinazolines [ 116 ].…”
Section: Classification Of Drugs Targeting Energy-metabolism In mentioning
confidence: 99%
“…The growing interest in ATP synthase as a target and the emerging of BDQ resistance has resulted in a number of HTS and in silico screenings to identify additional options for ATP synthase inhibition and novel chemical entities for medicinal chemistry optimization, such as epigallocatechin [ 114 ], thiazolidones [ 115 ], and diaminoquinazolines [ 116 ].…”
Section: Classification Of Drugs Targeting Energy-metabolism In mentioning
confidence: 99%
“…Recently, the solution Nuclear Magnetic Resonance (NMR) structure of the Mtb ε-subunit was resolved [56]. This structure, together with genetic and biochemical studies, showed that the Mtb ε-subunit plays a novel role in ATP synthesis by linking c-ring rotation to ATP synthesis at the α 3 β 3 -headpiece [56][57][58]. Critical to this function is the Mtb ε-subunit's inter-domain amino acid interaction network, which transmits information on c-ring rotation throughout the subunit and to its C-terminus.…”
Section: Disrupting the Mycobacterial F-atp Synthase ε-Subunit's Funcmentioning
confidence: 99%
“…The C-terminus can adopt an extended conformation to interact with the α 3 β 3 -headpiece to pass on this information. This process is proposed to contribute to the initiation of ATP synthesis at the α 3 β 3 -headpiece [56,58]. Through NMR titration, BDQ's binding site on the Mtb ε-subunit was uncovered to be the A10-W16 amino acid region [56].…”
Section: Disrupting the Mycobacterial F-atp Synthase ε-Subunit's Funcmentioning
confidence: 99%
“…The removal of its C-terminal resulted in an increased ATP hydrolysis rate and decreased ATP synthesis [86]. Furthermore, Saw et al, demonstrated that this site is amenable to chemical inhibition in M. smeg by epigallocatechin gallate, the most abundant catechin in green tea [87]. Other subunits involved in the regulation of ATP hydrolysis include the γand αsubunits of the F1 module [88,89].…”
Section: Atp Synthasementioning
confidence: 99%